Analisis Risiko Produksi Usaha Ayam Petelur di Kabupaten Tolitoli (Studi Kasus Desa Dadakitan, Kecamatan Baolan) - Dalle, Moeh Irsyad Fadhil AS. A.; Indah, Nur (Fakultas Peternakan Universitas Madako Tolitoli, 2025)
This study aims to analyze production risks faced by layer chicken farmers in Dadakitan Village, Baolan District, Tolitoli Regency, as well as the strategies implemented to overcome them. The research employed a qualitative approach with data collection techniques including in-depth interviews, observations, and documentation. The research informant was the owner of a layer chicken farm with a population of 7,000 birds producing an average of 3,000 eggs per day. The results revealed that the main risks in layer farming include human resources (HR), climate change, diseases, chicken mortality, environmental issues, and feed price fluctuations. These risks directly impact productivity decline and business sustainability. Strategies applied by farmers to mitigate these risks include developing standard operating procedures (SOP), conducting technical training, improving farm management, implementing biosecurity measures, administering vaccines and vitamins, maintaining environmental hygiene, and adjusting feed formulations with local ingredients. In conclusion, risk identification and the application of appropriate mitigation strategies can help farmers maintain productivity and ensure the sustainability of layer chicken farming in the study area.